ZAKIR NAIK’S SPEECH: THE USAGE OF HEDGES TO CHANGE ATTITUDE - NUGROHO, AZIZ (LANGUAGE HORIZON, 2018)
Abstract Persuasion or Attitude Change has been a main concern in the study of psychology. There have been many theories which evaluate the extent of variables in changing attitudes. However, none of them have conclusive results. Furthermore, the trend in the research of attitude change has been in the context of business or sales. There is very little to none research made to explain persuasion in religious sermons. Therefore, this study is meant to find how people could change their attitudes in religion. In particular, the subject used in this study is Zakir Naik, a well-known muslim proselytizer. He is well-versed in the field of comparative religion and has been holding talks and debates between religions. Many people from Christianity, Catholics, Hinduism etc. have become converts to Islam because of his speech. In this study, it was found that he used powerless language markers in order to persuade people into converting to Islam. He used powerless language markers to diminish Christianity and compliment Islam. Granted, with his vast knowledge of both theology he was capable of selecting certain verses in Christianity and proving that they are incoherent. Thus, people who once believed in Christianity, converted to Islam.Keywords: Persuasion, Attitudde Change, Religion, HedgesAbstrakPersuasi atau Attitude Change (perubahan pendirian) adalah suatu bahasan utama di bidang ilmu psikologi. Sudah ada beragam teori yang dibentuk untuk menentukan factor-faktor yang memengaruhi perubahan pendirian. Namun, belum ditemukan hasil yang konklusif. Selain itu, trend penelitian perubahan pendiriankebanyakan berada di konteks bisnis atau penjualan. Sangat sedikit sekali penelitian yang berfokus kepada ceramah keagamaan. Khususnya, subyek yang digunakan di dalam studi ini adalah Zakir Naik, seorang Dai Islam terkenal. Beliau sangat ahli di bidang perbandingan agama, dan beliau telah mengadakan acara dialog dan debat keagamaan. Banyak orang dari agama Kristen, Katolik, Hindu, dll. telah berpindah ke Islam dikarenakan ceramah beliau. Di studi ini, ditemukan bahwa beliau menggunakan hedges untuk membujuk orang masuk ke Islam. Beliau menggunakan hedges untuk mendiskreditkan ajaran agama Kristen dan memuji Islam. Tentu saja, dengan keluasan wawasannya atas ajaran teologi keduanya, beliau mampu memilih dan memilah suatu ayat di dalam Alkitab dan membuktikannya salah. Maka dari itu, penganut agama Kristen dapat terbujuk untuk masuk ke Islam.Kata kunci: Persuasi, Perubahan Pendirian, Agama, Hedges